Comparing national home-keeping and the regulation of translational stem cell applications: An international perspective. (March 2016) - Sleeboom-Faulkner, Margaret; Chekar, Choon Key; Faulkner, Alex; Heitmeyer, Carolyn; Marouda, Marina; Rosemann, Achim; Chaisinthop, Nattaka; Chang, Hung-Chieh (Jessica); Ely, Adrian; Kato, Masae; Patra, Prasanna K.; Su, Yeyang; et al.
Abstract: A very large grey area exists between translational stem cell research and applications that comply with the ideals of randomised control trials and good laboratory and clinical practice and what is often referred to as snake-oil trade. We identify a discrepancy between international research and ethics regulation and the ways in which regulatory instruments in the stem cell field are developed in practice. We examine this discrepancy using the notion of 'national home-keeping', referring to the way governments articulate international standards and regulation with conflicting demands on local players at home. Identifying particular dimensions of regulatory tools – authority, permissions, space and acceleration – as crucial to national home-keeping in Asia, Europe and the USA, we show how local regulation works to enable development of the field, notwithstanding international (i.e. principally 'western') regulation. Triangulating regulation with empirical data and archival research between 2012 and 2015 has helped us to shed light on how countries and organisations adapt and resist internationally dominant regulation through the manipulation of regulatory tools (contingent upon country size, the state's ability to accumulate resources, healthcare demands, established traditions of scientific governance, and economic and scientific ambitions). Highlights: Rather than ethical or rogue, the stem cell therapy field is a complex grey area. Wealth conditions the affordability of standards and stem cell strategies. Governments create different regulatory spaces for experimental research. Regulation for stem cell therapies can be designed to gain a competitive edge. Local and global stem cell organisations resist and undermine dominant ones.